PERANCANGAN DOKUMEN MUTU ISO 9001: 2008 DI PT âXâ - Jessica, Jessica; Sutapa, Nyoman (Jurnal Titra, 2015)
In this paper, we diagnosis the quality management system of ISO 9001: 2008âs clauses, particulary on PPIC and Production Department. We analyze the differences between the number of clauses which are not yet adopted before and after design the quality dokumen for the implementation of quality management system ISO 9001: 2008. The number of clauses after design the quality document which are not yet adopted decrease, i.e. 0% of quality management systemâs clause, 24% of management responsibilityâs clause, 3% of product realizationâs clause, and 46% of measurement, analysis and improvementâs clause.